2018
DOI: 10.3389/fmicb.2018.01601
|View full text |Cite
|
Sign up to set email alerts
|

An Uncharacterized Major Facilitator Superfamily Transporter From Planococcus maritimus Exhibits Dual Functions as a Na+(Li+, K+)/H+ Antiporter and a Multidrug Efflux Pump

Abstract: Within major facilitator superfamily (MFS), up to 27 unknown major facilitator families and many members of 60 well-characterized families have been functionally unknown as yet, due to their sharing no or significantly low sequence identity with characterized MFS members. Here we present the first report on the characterization of one functionally unknown MFS transporter designated MdrP with the accession version No. ANU18183.1 from the slight halophile Planococcus maritimus DS 17275T. During the screening of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 68 publications
3
30
0
1
Order By: Relevance
“…Accumulation of norfloxacin in E. coli CM2/pET-mdrP was found to be significantly enhanced by the addition of carbonyl cyanide m-chlorophenylhydrazone (CCCP), a proton gradient uncoupler. However, accumulation of norfloxacin in E. coli CM2/pET-mdrP was unable to reach the same maximum level as that of CM2/pET19 after the addition of CCCP (Abdel-Motaal et al, 2018). Considering MdrP being a Na + /H + antiporter, we hypothesize that MdrP may bind with Na + and therefore employ it as a coupling ion to drive norfloxacin efflux in a mode of drug/Na + antiport, similarly to those of Na + -coupled MATE transporters, N. gonorrhoeae NorM (Lu et al, 2013b) and V. cholerae NorM (Jin et al, 2014).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Accumulation of norfloxacin in E. coli CM2/pET-mdrP was found to be significantly enhanced by the addition of carbonyl cyanide m-chlorophenylhydrazone (CCCP), a proton gradient uncoupler. However, accumulation of norfloxacin in E. coli CM2/pET-mdrP was unable to reach the same maximum level as that of CM2/pET19 after the addition of CCCP (Abdel-Motaal et al, 2018). Considering MdrP being a Na + /H + antiporter, we hypothesize that MdrP may bind with Na + and therefore employ it as a coupling ion to drive norfloxacin efflux in a mode of drug/Na + antiport, similarly to those of Na + -coupled MATE transporters, N. gonorrhoeae NorM (Lu et al, 2013b) and V. cholerae NorM (Jin et al, 2014).…”
Section: Introductionmentioning
confidence: 90%
“…In our recent study (Abdel-Motaal et al, 2018), an uncharacterized MFS transporter from Planococcus maritimus has been identified to function as a Na + (Li + , K + )/H + antiporter and also as a multidrug efflux transporter with the resistance against multiple antimicrobial drugs, such as norfloxacin (Abdel-Motaal et al, 2018). In addition, this transporter was suggested to maybe belong to DHA1 family within MFS (Abdel-Motaal et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Purchased from Takara and then their growth was determined. The growth assay was conducted according to the protocol described by previous reports (Meng et al, 2017;Wang et al, 2017;Abdel-Motaal et al, 2018).…”
Section: Bacterial Strains and Plasmidsmentioning
confidence: 99%
“…Excitation wavelength was 500 nm (9-nm slit), and emission wavelength was 580 nm (20-nm slit). The EB efflux tests were performed according to the protocol as described by Abdel-Motaal et al [29], Reuter et al [8]and Balakrishnan et al [30].…”
Section: Fluorescence Testsmentioning
confidence: 99%
“…The excitation and emission wavelengths were 277 and 448 nm for norfloxacin. The norfloxacin accumulation test was performed as described by Abdel-Motaal et al [29].…”
Section: Fluorescence Testsmentioning
confidence: 99%